2019
DOI: 10.1038/s41438-019-0184-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple quantitative trait loci contribute to resistance to bacterial canker incited by Pseudomonas syringae pv. actinidiae in kiwifruit (Actinidia chinensis)

Abstract: Pseudomonas syringae pv. actinidiae (Psa) biovar 3, a virulent, canker-inducing pathogen is an economic threat to the kiwifruit (Actinidia spp.) industry worldwide. The commercially grown diploid (2×) A. chinensis var. chinensis is more susceptible to Psa than tetraploid and hexaploid kiwifruit. However information on the genetic loci modulating Psa resistance in kiwifruit is not available. Here we report mapping of quantitative trait loci (QTLs) regulating resistance to Psa in a diploid kiwifruit population, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
56
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 86 publications
3
56
1
Order By: Relevance
“…The distribution of Stab_Psa_score and Stem_necrosis across the population was Normal, whilst data for ooze, wilt and leaf spot were distributed in a non-Normal manner (Figure 6b-f). Normal distribution of the Stab_Psa_score was previously reported in a diploid A. chinensis population [38]. The analysis showed that greenhouse inoculation results are highly dependent on time of inoculation, similar to the earlier results for the diploid population [38], with clonal repeatabilities substantially lower than field repeatabilities.…”
Section: Stab Assaysupporting
confidence: 86%
See 1 more Smart Citation
“…The distribution of Stab_Psa_score and Stem_necrosis across the population was Normal, whilst data for ooze, wilt and leaf spot were distributed in a non-Normal manner (Figure 6b-f). Normal distribution of the Stab_Psa_score was previously reported in a diploid A. chinensis population [38]. The analysis showed that greenhouse inoculation results are highly dependent on time of inoculation, similar to the earlier results for the diploid population [38], with clonal repeatabilities substantially lower than field repeatabilities.…”
Section: Stab Assaysupporting
confidence: 86%
“…Normal distribution of the Stab_Psa_score was previously reported in a diploid A. chinensis population [38]. The analysis showed that greenhouse inoculation results are highly dependent on time of inoculation, similar to the earlier results for the diploid population [38], with clonal repeatabilities substantially lower than field repeatabilities. The best inoculated repeatability values were found for the sets inoculated in June (0.5) (winter) and the lowest for the sets inoculated in January (0.3) (summer).…”
Section: Stab Assaysupporting
confidence: 86%
“…savastanoi (Caballo-Ponce et al, 2016). Tissue-specific roles of T3Es have yet to be found in P. syringae, although varying resistance responses can occur between tissues (Tahir et al, 2019).…”
Section: How To Infec T Woody Tissue Smentioning
confidence: 99%
“…Broad-acting partial resistance to all clades exists in certain cultivars, notably Merton Glory (Hulin et al, 2018b). Perennial plants provide challenging study systems as differences in tissue-specific resistance, plant age, seasonal environment conditions, and nutrient status impact on susceptibility (Kus et al, 2002;Mur et al, 2017;Velásquez et al, 2018;Tahir et al, 2019).…”
Section: Towards Varie Tal Re S Is Tan Cementioning
confidence: 99%
See 1 more Smart Citation